2021
DOI: 10.1177/10781552211017193
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR 677T-1298C haplotype in acute lymphoblastic leukemia: Impact on methotrexate therapy

Abstract: Introduction Functional variants of the Methylenetetrahydrofolate reductase ( MTHFR) gene, the C677T and A1298C, have largely investigated in pharmacogenomics of Methotrexate (MTX) in acute lymphoblastic leukemia (ALL), yet the conclusions are inconsistent. In addition; most of these studies do not analyze haplotypes. Here, we investigate the MTHFR 677/1298 genotypes and the 677-1298 haplotype and characterize the MTX response in Northern African ALL patients. Methods Genomic DNA was extracted from whole venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The reason for delayed MTX excretion is worth exploring. Recently, growing evidence suggested that genetic variants of metabolic enzymes 11 , 12 or transporters 13 , 14 involved in MTX elimination could provide a mechanistic explanation for the variability of its pharmacokinetics. Furthermore, these variants might be potential predictors for personalized pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for delayed MTX excretion is worth exploring. Recently, growing evidence suggested that genetic variants of metabolic enzymes 11 , 12 or transporters 13 , 14 involved in MTX elimination could provide a mechanistic explanation for the variability of its pharmacokinetics. Furthermore, these variants might be potential predictors for personalized pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%